Transient Foetal Bradycardia in Primary Care: A Diagnostic Dilemma and Navigating Decision - Mohammad CM; Norhayaty SK; Nur Hafizah Ainaa AH (Asian Journal of Medicine & Health Sciences, 2024)
Transient foetal bradycardia is a rare occurrence during pregnancy, characterised by brief episodes of bradycardia followed by spontaneous resolution. Nevertheless, it is essential to exclude other causes, including sinus bradycardia, atrioventricular block, or auto-immune disease-related conditions. We report a case involving the incidental finding of transient foetal bradycardia in a 37-year-old woman at 20 weeks of gestation. A brief episode of foetal bradycardia was observed during a routine transabdominal ultrasound, with a heart rate of 82 beats per minute (bpm). After a short period of observation, foetal bradycardia recurred. The case was referred to a Maternal Foetal Medicine Specialist (MFM) in the obstetrics and gynecology department, where foetal echocardiography was conducted. The conclusion was that transient foetal bradycardia was likely secondary to prematurity. Repeated transabdominal ultrasound at 28 weeks of gestation revealed spontaneous resolution of foetal bradycardia. This case report highlights the importance of foetal cardiac surveillance during routine antenatal visits. The lack of access to foetal echocardiography makes it challenging to verify the diagnosis in primary care; hence, collaboration with a tertiary centre is essential.